Efektifitas Promosi Kesehatan Dengan Media Leaflet dan Video Terhadap Pengetahuan dan Sikap Pasien Tentang Pencegahan Jatuh di Ruang Rawat Inap RSAB Harapan Kita Jakarta 2024 - Surastiningsih, Neneng; Ulfa, Laila; Aprillia, Yuna Trisuci (Jurnal Untuk Masyarakat Sehat (JUKMAS), 2025)
Background: Health promotion interventions using leaflets and videos are educational efforts for fall prevention, with nine fall cases reported at RSAB Harapan Kita in 2022. This study aimed to determine the effectiveness of health promotion through leaflets and videos on patients' knowledge and attitudes regarding fall prevention in the inpatient wards of RSAB Harapan Kita Jakarta. Methods: This study employed a quasi-experimental design with a two-group pretest-posttest design, measuring knowledge and attitude variables in the leaflet and video groups. Conducted in June 2024 at RSAB Harapan Kita Jakarta, the study included 33 respondents in the leaflet group and 33 respondents in the video group selected using accidental sampling techniques. Data analysis was performed using paired T-tests, encompassing univariate and bivariate analysis. Results: The results of the health promotion regarding fall prevention at RSAB Harapan Kita indicated that the use of leaflets significantly increased patient knowledge (p=0.000). However, it did not have a meaningful impact on patient attitudes (p=0.179). In contrast, the use of video media was effective in enhancing both knowledge (p=0.000) and patient attitudes (p=0.035) towards fall prevention. Conclusion: This study concluded that health promotion using leaflets effectively enhanced patient knowledge, though it did not significantly alter patient attitudes toward fall prevention at RSAB Harapan Kita. Conversely, promotion through video media significantly influenced both knowledge and attitudes of patients regarding fall prevention.